Pengaruh Kesadaran Wajib Pajak, Sanksi Administrasi Dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak Generasi Millenial Di Kota Padang - Muhammad Aidi Akbar; Nurzi Sebrina; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
The research has the purpose to find the effect of taxpayer’s awareness, tax penalties, and taxpayers knowledge towards taxpayer’s compliance of millenials generation in Padang. The data obtained troughs questionnaire, and sample were drawn from 100 of taxpayers that select as millenials generation in Padang. The data analyzed by using SPSS 16. In this research there are two variables, those are independent variable which is taxpayer’s awareness, tax penalties, taxpayers knowledge and the dependent variable which is taxpayer’s compliance. The finding indicated that taxpayer’s awareness has positive effect toward taxpayer’s compliance, Tax penalties has positive effect towards toward taxpayer’s compliance, Taxpayer’s knowledge has positively effect towards taxpayer’s compliance